Stabilization analysis for fuzzy systems with a switched sampled-data control. Issue 1 (January 2020) - Luo, Jinnan; Li, Mengling; Liu, Xinzhi; Tian, Wenhong; Zhong, Shouming; Shi, Kaibo
Abstract: This study focuses on the stabilization analysis for fuzzy systems with the switched sampled-data control. By utilizing the information of the membership functions, an improved time-dependent and fuzzy-membership-function-dependent Lyapunov–Krasovskii functional (LKF) is constructed to commendably capture the available information related to the real sampling pattern. Together with a switching idea and newly inequalities, further results with less conservativeness are established to ensure that the switched sampled-data control stabilizes the fuzzy systems. Moreover, the switched sampled-data controllers are devised with a larger sampling interval. Finally, the effectiveness of the presented criteria is verified by two examples.